“Mannequin/Mankind Culture”: Mempertanyakan “Ada” pada Manekin dan Manusia - Luthfi Adam (Jurnal Komunikasi)
Mannequins attract consumers in every stores and malls. They stand silently, but “speak” loudly to us. They are not just statues, because there are some signs, images, values, and knowledge beyond these phenomena. This article studies the meaning of mannequin in mankind culture based on Heidegger's thought about “being”. Then, seeks the relation of this phenomenon to representation and cultural homogenization.